Enhanced Human T Lymphocyte Antigen Priming by Cytokine-Matured Dendritic Cells Overexpressing Bcl-2 and IL-12 - Zhang, Hui; Wang, Yu; Wang, Qian-Ting; Sun, Sheng-Nan; Li, Shi-You; Shang, Hong; He, You-Wen (Frontiers in Cell and Developmental Biology, 2020)
Dendritic cells (DCs) based vaccination is a promising cancer immunotherapeutic strategy, however, clinical trials have shown only limited efficacy, suggesting a need for optimizing the protocols of human DC vaccine preparation. In this study, we systemically compared 5 different human DC vaccine maturation protocols used in clinical trials including 1. a four-cytokine cocktail (TNF-α/IL-6/IL-1β/PGE2), 2. An α-DC-cytokine cocktail (TNF-α/IL-1β/IFN-α/IFN-γ/Poly I:C), 3. LPS/IFN-γ, 4. TNF-α/PGE2 and 5. TriMix (DCs electroporated with mRNA encoding CD70, CD40L and a constitutively active toll-like receptor 4 (caTLR4). We found that the four-cytokine cocktail induced high levels of costimulatory molecules and HLA molecules, as well as CCR7 on DCs. The viability of mature DC (mDC) matured with the four-cytokine cocktail was higher than the other protocols. Based on these features, we chose the four-cytokine cocktail protocol to further improve DC immunizing capability by introducing exogenous genes. We show that introducing exogenous Bcl-2 increased DC survival. Furthermore, introducing interleukin (IL)-12p70 could rescue the inhibition of the IL-12 secretion by PGE2 without impairing DC’s phenotype. Introducing both Bcl-2 and IL-12p70 into DCs induced enhanced cytomegalovirus (CMV) pp65-specific CD8+ T cells secreting IFN-γ and TNF-α. Taken together, our data suggest that DC maturated by the four-cytokine cocktail combined with exogenous Bcl-2 and IL-12p70 gene expression represents a promising approach that is ready for clinical application in cancer immunotherapy.